Dietary bile acids supplementation modulates immune response, antioxidant capacity, glucose, and lipid metabolism in normal and intrauterine growth retardation piglets - Liu, Yang; Azad, Md. Abul Kalam; Kong, Xiangfeng; Zhu, Qian; Yu, Zugong (Frontiers in Nutrition, 2022)
Intrauterine growth retardation (IUGR) results in intestinal dysfunction contributing to metabolic syndrome and growth lag of piglets. Bile acid (BA) presents various bioactivities, including regulation roles in antioxidant, anti-inflammation, and glucose and lipid metabolism. Forty-eight weaned piglets were allocated to four groups in a 2 × 2 factorial arrangement with the effects of BA supplementation and IUGR challenge. Twenty-four IUGR piglets and 24 normal birth weight (NBW) piglets were allocated into two groups, respectively, including the control group fed with a basal diet, and the treatment group fed a basal diet supplemented with 400 mg/kg BA. The experiment lasted 28 days. The results indicated that BA improved liver and spleen indexes in IUGR piglets, whereas decreased blood RDW-CV and RDW-SD regardless of IUGR (P < 0.05). Dietary BA supplementation decreased plasma CAT activity and liver GSH concentration regardless of IUGR, whereas increased plasma GSH and liver H2O2 and decreased liver T-AOC in weaned piglets (P < 0.05). In addition, IUGR downregulated liver Nrf1 and Nrf2 expression levels, while BA supplementation upregulated the Nrf2 expression of liver in weaned piglets (P < 0.05). Dietary BA decreased (P < 0.05) jejunal GSH concentration and ileal CAT activity regardless of IUGR. Furthermore, IUGR upregulated (P < 0.05) jejunal SOD and CAT expression levels; however, dietary BA upregulated ileal Nrf1 (P < 0.05) and Keap1 (P = 0.07) expression levels in piglets regardless of IUGR. Moreover, IUGR upregulated the liver lipid synthesis (FAS) and downregulated HSL and SCD1 expression levels, while dietary BA downregulated liver FAS and SCD1 expression levels (P < 0.05). However, BA supplementation could enhance liver gluconeogenesis by upregulating (P < 0.05) the liver G6PC and PCK1 expression levels in the NBW piglets but not in the IUGR piglets. Collectively, these findings suggest that BA could regulate the redox status of weaned piglets by regulating the Nrf2/Keap1 pathway and improving liver glucose and lipid metabolism of IUGR piglets. These findings will provide a reference for the application of BA in swine production; moreover, considering the physiological similarity between pigs and humans, these findings will provide a reference for IUGR research in humans.